Razširjenost gesljenja leposlovja v osnovnošolskih knjižnicah - Hribernik, Alenka (Šolska knjižnica, 2012)
Subject description of fiction is an important part of processing library material in primary school libraries. Subject headings make library material more accessible, thus it is more likely for library users to find a book with a specific subject by themselves or with librarian's help. In this way we stimulate reading and educate pupils to become independent and active library users, which is one of the basic goals of school libraries. The aim of the study was to establish how often subject description of juvenile literature was used in primary school libraries. The survey included 77 primary schools in Slovenian municipalities. The analysis of the results has shown that the majority of librarians (81%) define subject headings for works of fiction. They mostly use them to describe main themes; many of them also add formal descriptions and descriptions defining target audience. 79% of librarians share the opinion that subject description is a very important part of book description (rated with marks 4 and 5). 67% of librarians support the idea of uniting knowledge and experience to make common guidelines for formation of subject headings. This shows that primary school librarians are also aware of the fact that subject description should enable readers to fulfil their information needs by using subject headings. Our suggestion is to conduct additional researches in order to study users of primary school libraries and according to the results create a model of subject description of juvenile literature for primary schools. We should focus our attention on creating the user interface which would enable faster and easier training of pupils as independent library users. Only in this way subject description of fiction would fully serve.
Keywords: gesla; klasifikacija; knjižnični katalogi; leposlovje; osnovne šole; predmetne oznake; raziskave; šolske knjižnice; vsebinska obdelava